2011
DOI: 10.5489/cuaj.11134
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer screening: Canadian guidelines 2011

Abstract: A systematic literature search was conducted in the following electronic bibliographic databases: MEDLINE, including PreMedline (2004 to November 2010), EMBASE (2004 to Week 44, 2010 and the Cochrane Central Register of Controlled Trials (2010, 4th Quarter). This search was restricted to studies published in English.The search queries were based on a combination of exploded and non-exploded subject headings and free-text keywords. These terms included prostate cancer, prostatic neoplasms, prostate tumour, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 73 publications
1
45
0
Order By: Relevance
“…There is an obvious need among family physicians for conclusive evidence on the balance of screening benefits and harms. The modern use of adjuncts to a single PSA cut-off, in addition to active surveillance of low-risk cancers, 11 exceeds the scope of conclusions drawn from recent randomized trials. It is unlikely that a consensus on the utility of prostate cancer screening will be achieved until randomized studies with long durations of follow-up evaluate modern screening practices.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…There is an obvious need among family physicians for conclusive evidence on the balance of screening benefits and harms. The modern use of adjuncts to a single PSA cut-off, in addition to active surveillance of low-risk cancers, 11 exceeds the scope of conclusions drawn from recent randomized trials. It is unlikely that a consensus on the utility of prostate cancer screening will be achieved until randomized studies with long durations of follow-up evaluate modern screening practices.…”
Section: Resultsmentioning
confidence: 97%
“…Unfortunately, the results of these trials published in 2009 are conflicting, with the PLCO failing to demonstrate a survival benefit and the ERSPC demonstrating a 20% mortality reduction attributable to screening men aged 55 to 69. Although methodological differences may account for the discordant results, 11,12 the question of screening utility is as contentious as ever.…”
Section: Introductionmentioning
confidence: 99%
“…Searching PubMed, Medline, and Embase yielded 348 papers, 30 of which met the inclusion criteria for study selection (two systematic reviews, 8,9 two meta-analyses, 6,10 five literature reviews, 2,4,5,11,12 and 21 single-study papers 3,13-32 ) (Fig. 1).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Active surveillance (AS) has been proposed as a strategy to decrease overtreatment [4][5][6][7][8][9][10] and is now recognized as a management option by a number of evidence-based guidelines. [11][12][13] Although several prospective series have reported on its safety, 4-10 few studies have reported on the uptake of AS at a population level. [14][15][16][17][18][19][20][21][22][23] No previous population-based study has evaluated the proportion of men being managed by AS in Canada.…”
Section: Introductionmentioning
confidence: 99%